1983
DOI: 10.1207/s15327752jpa4702_7
|View full text |Cite
|
Sign up to set email alerts
|

Rorschach Norms for Inner City Children

Abstract: Rorschach data for 272 Black children are presented in age groups from 3 to 12. The Rorschach characteristics presented are F+%, A%, Fabulized Combinations, Perseverations, Color Naming, Rejections, Wholes, Details, Small Details (Dd), R, M, and P. Comparisons with Ames and Exner reveal a lower form accuracy level, and a lower percentage of Wholes, with a higher D level. Response rate, rate of development of the M response, rate of development of the P response, and of the Animal response are very similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The studies by Brault and Laveault (1992), Ihanus et al (1992), and Zucker et al (1992) were not included in Table 8 here. Each had obstacles to including them, for example, no CS variables, criterion-valid subject pool, non-CS administration procedures, and so on Studies by Krall et al (1983) and Cotugno (1995) were included, although they did not contain full CS data for their samples. Table 8 juxtaposes key available data from the CS, the Krall and Cotugno studies, and this study.…”
Section: % Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Brault and Laveault (1992), Ihanus et al (1992), and Zucker et al (1992) were not included in Table 8 here. Each had obstacles to including them, for example, no CS variables, criterion-valid subject pool, non-CS administration procedures, and so on Studies by Krall et al (1983) and Cotugno (1995) were included, although they did not contain full CS data for their samples. Table 8 juxtaposes key available data from the CS, the Krall and Cotugno studies, and this study.…”
Section: % Agreementmentioning
confidence: 99%
“…Prior to this research, a small number of journal articles presented Rorschach data for nonpatient children (Brault & Leveault, 1992;Cotugno, 1995;Ihanus, Keinon, & Vanhamaki, 1992;Krall et al, 1983;& Zucker, Lozinski, Bradley, & Doering, 1992.). In each, the nonpatient data were used for comparison to a criterion-valid, pathological sample that was the primary focus of the study.…”
mentioning
confidence: 99%
“…Fur ther more, there have been a sub stan tial num ber of cri tiques re gard ing cross-cul tural use of the Ror schach and par tic u larly the lack of ap pro pri ate nor ma tive data (for summa ries of this lit er a ture, see Garb et al, in press;Wood & Lilienfeld, 1999). For ex am ple, Krall et al (1983) found that inner-city black chil dren dif fered from then-cur rent CS norms on 5 (50%) of 10 Ror schach vari ables. Glass, Bieber, & Tkachuk (1996) …”
Section: Use Of the Cs With American Minority Groups Or Non-americansmentioning
confidence: 99%
“…Lower-class and middle-class adults and children also differ in aggregate scores on Rorschach. For instance, lower-class adults show a higher percentage of responses in which form is a determinant, and Black lower-class children show a lower form level and a higher W% (Exner, 1974;Fiedler & Stone, 1956;Krall et al, 1983).It should be noted that the differences reported in the literature have all been on rather crude measures (e.g., length of story, presence of a family figure, aggregate scores) and generally have not been interpreted in terms of the underlying personality differences that might have produced them. There is, however, a separate body of literature that suggests that there are differences in modal personality among individuals from various social classes.…”
mentioning
confidence: 99%
“…Lower-class and middle-class adults and children also differ in aggregate scores on Rorschach. For instance, lower-class adults show a higher percentage of responses in which form is a determinant, and Black lower-class children show a lower form level and a higher W% (Exner, 1974;Fiedler & Stone, 1956;Krall et al, 1983).…”
mentioning
confidence: 99%